STUDY OF TRANSIENT STATES IN NEWBORN INFANTS DURING THE ADAPTATION PERIOD - Rasulova Saodat Khalimovna (Modern American Journals, 2025)
This article analyzes transient conditions observed in newborns during the adaptation period. Physiological jaundice, transient intestinal and endocrine changes, and immunological adaptation processes are studied. The goal is to distinguish physiological and pathological conditions, avoid overtreatment, and ensure healthy development.
Keywords: Newborn, adaptation period, transient state, physiological jaundice, immunity, endocrine system.